Agapanthus allergic contact dermatitis: A case report - Horiuchi, Yasuhiro (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Agapanthus (Lily of the Nile) is a genus in the flowering plant family Amaryllidaceae. Contact dermatitis caused by flowering plants is common, but there are no reports of contact dermatitis caused by this plant, Agapanthus. Case Illustration: An 82-year-old Japanese man had cultivated Agapanthus in his home garden. After breaking the stem of the leaf while wearing shorts, he noticed erythematous rashes on the thighs. The patch test of the leaf stem sap “as is” showed mildly positive, with erythematous papules. Discussion: The patch test confirmed the allergic contact dermatitis of Agapanthus with leaf stem sap. There are many well-known flowering plants, like lilies, daisies, jasmine, orchids so on, that can cause contact dermatitis. To date, many people fold Agapanthus flowers and decorate them at home, so far, this plant should also be added to the causative plant for contact dermatitis. Conclusion: To the best of our knowledge, there are no reports of contact dermatitis caused by this plant. Agapanthus contact dermatitis will need to be brought to people’s attention.